Influence of the connecting rod on the biomechanical properties of five external skeletal fixation configurations - Bronson, D. G.; Ross, J. D.; Toombs, J. P.; Welch, R. D. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
A recently developed external skeletal fixation system (SK™, IMEX Veterinary, Inc.) utilizes larger diameter connecting rods, therefore overcoming one of the weaknesses of the original Kirschner-Ehmer (KE) system. The purpose of the current study was to compare five typical external fixator constructs in axial compression, torsion, Cranial-Caudal (C-C) and Medial-Lateral (M-L) bending to determine the effect of the larger connecting rods on frame stiffness. The results demonstrate that the larger connecting rod has a significant effect on overall frame stiffness. The use of two or more full-pins, as in the type II and III techniques nullified the contribution of the connecting rod diameter and frame stiffness was more a factor of pin size, number and orientation.
Keywords: External fixation; biomechanics; Kirschner-Ehmer; SK™; connecting rod